The potential of microRNA‐126 in predicting disease risk, mortality of sepsis, and its correlation with inflammation and sepsis severity. Issue 9 (2nd June 2020) - Lin, Run; Hu, Haiyan; Li, Lehui; Chen, Gengqian; Luo, Lingqing; Rao, Ping
Abstract: Background: MicroRNA‐126 (miR‐126) has been investigated in autoimmune diseases and organ failures, whereas its implication in sepsis is rarely reported. Our study initially explored the value of miR‐126 in diagnosing sepsis and predicting disease severity, degree of inflammation, and mortality. Methods: Totally, 208 sepsis patients and 210 healthy controls were enrolled; then, their plasma samples were collected for detecting circulating miR‐126 by quantitative polymerase chain reaction. For sepsis patients, their cytokine levels in plasma samples were detected by enzyme‐linked immunosorbent assay. Results: miR‐126 was upregulated in sepsis patients compared with healthy controls, and it was of certain value in distinguishing sepsis patients from healthy controls (AUC: 0.726 (95% CI: 0.678‐0.774)). miR‐126 expression was positively correlated with acute physiology and chronic health evaluation II score, serum creatinine, and C‐reactive protein but not albumin or white blood cell count in sepsis patients. Regarding cytokines, miR‐126 was positively correlated with tumor necrosis factor‐α, interleukin (IL)‐6, and IL‐8, but negatively correlated with IL‐10 in sepsis patients. As for mortality, miR‐126 expression was higher in deaths compared with survivors, and ROC curve displayed that it could predict mortality of sepsis patients to some extent with AUC of 0.619 (95% CI: 0.533‐0.705). Conclusion: miR‐126 potentially serves as an assistant diagnostic and prognostic biomarker for sepsis.